PENGARUH KEPEMILIKAN MAYORITAS, PROFITABILITAS, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (PERUSAHAAN YANG MEMENANGKAN CORPORATE SOCIAL RESPONSIBILITY AWARDS (ICSRA) 2021) - Caroline La Viola; Sekar Mayangsari (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This study aims to determine majority ownership, profitability, company size, and company age on the disclosure of Corporate Social Responsibility in publicly listed companies on the Stock Exchange for the 2018-2021 period and win the 2021 Corporate Social Responsibility Awards (ICSRA). This study used a sample of 20 company premises purposive sampling techniques. The data analysis technique used is the Classical Assumption Test, namely the Error Normality Test, Autocorrelation Test, Multicollinearity Test, and Heteroscedasticity Test, and continued with the Theory Test, namely the Coefficient of Determination Test, F Statistics Test, and T Statistical Test. The results of this study partially show that Majority Ownership and Profitability have a significant effect on the disclosure of Corporate Social Responsibility disclosures, besides Company Size has no significant effect on Corporate Social Responsibility Disclosure and Company Size does not have a significant negative effect on Corporate Social Responsibility disclosure. In addition, the results of this study simultaneously majority ownership, profitability, company size, and company age have a significant effect on the disclosure of Corporate Social Responsibility.